EKSPLORASI TEMA DAN RESPONS WARGANET TERHADAP KEBENCANAAN DI INSTAGRAM: SEBUAH STUDI NETNOGRAFI PADA UNGGAHAN ERUPSI GUNUNG LEWOTOBI - Ningrum, Anisa Purwa; Arisandy, Rita; Rahmandari, Ismi Arifiana; Wijaya, Arya Ananta (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
This study explores the responses of Indonesian netizens to the eruption of Mount Lewotobi on Instagram. Using a qualitative approach with a netnographic method, this research observes netizen conversations in the comment sections of five viral posts related to the disaster. Data were purposively collected, with a sample of 139 comments from a total of 695 comments. The findings reveal five major themes of conversation or netizen responses: (1) religious and social, which include religious responses to the disaster and criticism of local behavior; (2) cognitive and interpretative views on the disaster, which include historical comparisons, validation and interpretation of the disaster’s impact, field observations, access to natural tourism safety, political interpretations of the disaster, and humorous responses to the disaster; (3) disaster mitigation, which includes disappointment with disaster mitigation and criticism of the government; (4) media and information, which covers media imbalance, doubts about information, selectivity of information, and the aesthetics of documentation; and (5) public mobility, which includes netizen responses to the impact of the disaster on mobility and transportation. The research findings also highlight the role of social media as an alternative source of information and a space for public criticism, as well as revealing challenges related to misinformation and disaster aesthetics in digital space. This study reinforces the urgency of developing disaster communication that educates, buids awareness, fosters sympathy and empathy, and cultivates public solidarity in the digital space. The goverment and disaster-related agencies can use the research results to manage disaster information disseminated to netizens on social media and to respond more responsively to netizen dynamics when a disaster occurs. Keywords: Disaster Communication, Indonesian Netizen Responses, Lewotobi Eruption, Social Media, Netnography